2005
DOI: 10.1038/nm1269
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular protein therapy with SOCS3 inhibits inflammation and apoptosis

Abstract: Suppressor of cytokine signaling (SOCS) 3 attenuates proinflammatory signaling mediated by the signal transducer and activator of transcription (STAT) family of proteins. But acute inflammation can occur after exposure to pathogen-derived inducers staphylococcal enterotoxin B (SEB) and lipopolysaccharide (LPS), or the lectin concanavalin A (ConA), suggesting that physiologic levels of SOCS3 are insufficient to stem proinflammatory signaling under pathogenic circumstances. To test this hypothesis, we developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
216
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(228 citation statements)
references
References 29 publications
10
216
2
Order By: Relevance
“…The absence of proinflammatory cytokine induction could be partly due to the parallel elevation of the SOCS-3 mRNA after infection. The SOCS-3 is a potent inhibitor of cytokine signaling and its transgenic over-expression may inhibit inflammation and associated apoptosis in vivo (Auerhammer and Melmed, 2001;Jo et al, 2005). Accordingly, although infected mice had elevated basal pro-inflammatory cytokine levels (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of proinflammatory cytokine induction could be partly due to the parallel elevation of the SOCS-3 mRNA after infection. The SOCS-3 is a potent inhibitor of cytokine signaling and its transgenic over-expression may inhibit inflammation and associated apoptosis in vivo (Auerhammer and Melmed, 2001;Jo et al, 2005). Accordingly, although infected mice had elevated basal pro-inflammatory cytokine levels (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the effect of infection on ischemic damage may largely depend on the regulation of reactive oxygen species by pro-inflammatory and anti-inflammatory cytokines as well as by the main antioxidant state regulators, namely superoxide dismutase (SOD) (Guegan et al, 1998;Murakami et al, 1998), glutathione (GSH) (Nicholls and Budd, 2000;Schulz et al, 2000;Droge, 2002), uncoupling protein-2 (UCP2) (Arsenijevic et al, 2000b;Mattiasson et al, 2003) and nerve growth factor (NGF) (Brodie, 1996;Guegan et al, 1999;Villoslada et al, 2000). In addition, the newly described suppressor of cytokine signaling (SOCS) proteins are induced in peripheral and central models of inflammation (Lebel et al, 2000;Bates et al, 2001;Larsen and Ropke, 2002;Wang and Campbell, 2002;Huang et al, 2003;Park et al, 2003;Jo et al, 2005). SOCS possibly interact with cellular redox determinants (Park et al, 2003) and transgenic SOCS expression has been shown to inhibit inflammation and apoptosis following lipopolysaccharide (LPS) injection (Jo et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although SOCS3 knockout mice die in utero due to placental defects, conditional SOCS3 depletion induces inflammatory and metabolic disorder [49][50][51]. Thus, SOCS3 plays a role in cytokine as well as insulin signaling.…”
Section: Socs3mentioning
confidence: 99%
“…Penetratin has been shown to cause uniform distribution and improve tumor retention of single-chain antibody marking an important step toward radio immunotherapy of solid tumors. Recombinant SOCS3-CPP has been shown to effectively inhibit the cytokine-mediated signal transduction associated with acute inflammation and liver apoptosis (67). Disulfide linkage between Tat and anti-tetanus antibody caused neutralization of the toxin and showed higher nuclear localization (68).…”
Section: Delivery Of Proteins As Cpp-cargo Complexmentioning
confidence: 99%